CHARACTERIZATION OF CASSAVA (MANIHOT SCULENTA CRANTZ) AERIAL PARTS FOR RUMINANT FEEDING - SALLES, M. S. V.; BONILHA, S. F. M.; FELTRAN, J. C.; VALLE, T. L.; RODRIGUES, M. M. F. C.; KANTHACK, R. A. D.; ROMA JUNIOR, L. C. (Ars Veterinaria, 2016)
The objective of this research was to characterize the chemical composition and digestibility of aerial part and cuttings of four cassava cultivars grown in five different levels of soil fertilization and three plant densities, in order to use the residues for ruminant feeding. The experiment was conducted using a randomized complete block design, in strip-split-plot scheme, with four replicates. The plots were composed of IAC14, IAC15, IAC90, and Cascuda cultivars; the subplots consisted of five fertilization categories, one fertilization with poultry litter (3000 kg.ha-1) and four chemical fertilization rates (0, 150, 450, 900 kg.ha-1) with NPK 4-20-20; and with the sub-subplots consisted of three plant densities (7,500, 12,500, 17,500 plants.ha-1). During the experiment, aerial part and cuttings were sampled for chemical and in vitro digestibility analyzes. There were differences between the varieties of cassava and fertilization rates on fiber fractions, chemical composition, in vitro digestibility, total digestible nutrients (TDN), and dry matter yield (kg / ha) of aerial part (P<0.05) and cuttings (P<0.05). Cassava aerial part and cuttings have considerable amounts of nutrients that can be used for ruminant feeding on small farms and for animal categories with low nutritional requirements. From all treatments, variety IAC15, with chemical fertilization of 900 kg.ha-1, as well as fertilization with poultry litter, with the highest plant density, were those with better nutritional composition and greater amount of available nutrients.